Function and regulation of ubiquitin-like SUMO system in heart - Wang, Ying; Liu, Zhihao; Bian, Xiyun; Zhao, Chenxu; Zhang, Xin; Liu, Xiaozhi; Wang, Nan (Frontiers in Cell and Developmental Biology, 2023)
The small ubiquitin-related modifier (SUMOylation) system is a conserved, reversible, post-translational protein modification pathway covalently attached to the lysine residues of proteins in eukaryotic cells, and SUMOylation is catalyzed by SUMO-specific activating enzyme (E1), binding enzyme (E2) and ligase (E3).Sentrin-specific proteases (SENPs) can cleave the isopeptide bond of a SUMO conjugate and catalyze the deSUMOylation reaction. SUMOylation can regulate the activity of proteins in many important cellular processes, including transcriptional regulation, cell cycle progression, signal transduction, DNA damage repair and protein stability. Biological experiments in vivo and in vitro have confirmed the key role of the SUMO conjugation/deconjugation system in energy metabolism, Ca 2+ cycle homeostasis and protein quality control in cardiomyocytes. In this review, we summarized the research progress of the SUMO conjugation/deconjugation system and SUMOylation-mediated cardiac actions based on related studies published in recent years, and highlighted the further research areas to clarify the role of the SUMO system in the heart by using emerging technologies.